Pineapple Leaf Fiber and Polyester Fabric Composite as a Material for Transtibial Prosthetic Socket Fabrication - Supadma, Deby Eka; Rahmawati, Rina Fitriana; Kristianto, Jusuf (Poltekkes Kemenkes Jakarta I, 2025)
Background: A transtibial prosthesis restores mobility and functionality for individuals with below-knee amputations, with the socket serving as a vital interface between the residual limb and the prosthesis. In Indonesia, prosthetic sockets are commonly made from plastic, valued for strength and durability but criticized for non-sustainability, and high import costs. Locally sourced and cost-effective materials, such as pineapple leaf fiber, have gained attention as sustainable alternatives, offering lightweight and durable solutions. However, the natural fiber’s appearance may impact amputee satisfaction. Combining pineapple leaf fibers with polyester fabric could address these limitations by improving aesthetics without compromising functionality. Aims: This study aimed to develop and evaluate a transtibial prosthetic socket fabricated from pineapple leaf fibers and polyester fabric, focusing on accessibility, affordability, and enhanced usability for Indonesian amputees. Methods: The study used a quantitative experimental design that included creating composite materials with specific ratios of pineapple leaf fiber, epoxy resin, and polyester fabrics and fabricating transtibial prosthetic sockets using the lamination method. The socket was fitted to a transtibial amputee to ensure proper alignment and function. Over six weeks, the participant used the prosthesis in daily activities while data was collected on comfort, durability, and walking performance, along with feedback through interviews and questionnaires. Results: Amputee demonstrated improved mobility in daily activities, with slight endurance limitations during extended walking. Satisfaction was high regarding comfort, fit, aesthetics, and reliability. Conclusion: The composite material is a viable alternative for transtibial sockets, promoting sustainability and accessibility. Refinements for endurance and broader applications of natural fibers are recommended.